Major traits of the senescent phenotype of nucleus pulposus intervertebral disc cells persist under the specific microenvironmental conditions of the tissue. (January 2019) - Kouroumalis, Anastasios; Mavrogonatou, Eleni; Savvidou, Olga D.; Papagelopoulos, Panayiotis J.; Pratsinis, Harris; Kletsas, Dimitris
Highlights: Conditions met in the disc environment are anti-proliferative for IVD cells. Classical markers of senescence are preserved by disc cells under IVD conditions. Enhanced catabolic activity of senescent disc cells persists under IVD conditions. Abstract: Intervertebral discs (IVDs) are the joints of the spine, mainly consisting of extracellular matrix (ECM) with a low number of cells embedded therein. Low cellularity stems from nutrient deprivation due to the lack of blood supply, as well as from the hypoxic and hyperosmotic conditions prevailing in the tissue. Intervertebral disc degeneration (IDD) has been firmly connected with low back pain, a major age-related disease, whereas degenerated discs have been characterized by increased proteolytic activity and accumulation of senescent cells. While the catabolic phenotype of senescent IVD cells has been documented, whether this phenotype is preserved under the harsh conditions met in the IVD milieu has never been investigated. Here we showed that a combination of low glucose, hypoxia, high osmolality and absence of serum is anti-proliferative for young disc cells. In addition, we demonstrated for the first time that classical senescence markers, namely p16 INK4a, p21 WAF1 and ICAM-1, remain up-regulated in senescent cells under these conditions. Finally, up-regulation of the main senescence-associated ECM degrading enzymes, i.e. MMP-1, -2 and -3 was maintained in this strict environment. Conservation of IVD cells' senescent phenotype under the actual conditions these cells are confronted with in vivo further supports their possible implication in IDD.